Differential deformation of gravity-driven deep-water fold-and-thrust belts along the passive continental margin of East Africa and their impact on petroleum migration and accumulation. (February 2020) - Cai, Jun; He, Youbin; Liang, Jianshe; Qiu, Chunguang; Zhang, Can
Abstract: Passive-margin deep-water fold-and-thrus belts (DWFTBs) have been the focus of a number of studies in recent decades because many oil and gas fields have been discovered in traps associated with them. Nevertheless, the impact of DWFTBs on petroleum plays remains unclear. In this study, we developed models for petroleum migration and accumulation in the offshore Rovuma Basin and Lamu Basin DWFTBs located along the passive continental margin of East Africa based on an integrated analysis of seismic, geochemical and geological data. Using available high-quality seismic data in the depth domain, we were able to quantify the evolution of thrust anticline growth by applying the area-depth-strain (ADS) method. Our results indicate that the offshore Lamu Basin DWFTB was active from the late Cretaceous period to the early Miocene period, while the offshore Rovuma Basin DWFTB has been active from the Oligocene period. Geochemical parameters and basin modeling show that widespread lower Jurassic mudstone is the dominant source of petroleum resources, with peaks of oil and gas generation in the Cretaceous and Cenozoic periods, respectively. Based on this, we suggest that the traps within the offshore Lamu Basin DWFTB contain oil generated from lower Jurassic sources that migrated along faults and accumulated during the late Cretaceous period and gas generated from the same sources during the Cenozoic period. Conversely, there is an insufficient amount of oil in the offshore Rovuma Basin DWFTB owing to the absence of oil migration pathways or traps as a result of the DWFTB's more recent formation from the Oligocene period. Highlights: Differences between Rovuma DWFTB and Lamu DWFTB are researched comparatively. Dominant source rocks in eastern African passive continental margin are pointed out. That differences of DWFTBs deformation timings control petroleum migration and accumulation is suggested.